HSP70 Content in Blood Serum of Patients with Chronic Polypoid Rhinosinusitis - Onishchenko, A. I.; Tkachenko, A. S.; Kharchenko, E. A.; Sklyaruk, D. O. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 181